2017
DOI: 10.1016/j.physrep.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Temperature in and out of equilibrium: A review of concepts, tools and attempts

Abstract: We review the general aspects of the concept of temperature in equilibrium and non-equilibrium statistical mechanics. Although temperature is an old and well-established notion, it still presents controversial facets. After a short historical survey of the key role of temperature in thermodynamics and statistical mechanics, we tackle a series of issues which have been recently reconsidered. In particular, we discuss different definitions and their relevance for energy fluctuations. The interest in such a topic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
147
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(161 citation statements)
references
References 300 publications
5
147
0
Order By: Relevance
“…They have concluded that under the local equilibrium condition, different definitions give the same temperature, while in a non-equilibrium state beyond local equilibrium, the values of temperature defined by different approaches may deviate from one another. Puglisi et al have reviewed different definitions of temperature in classical systems and discussed their relevance to energy fluctuations [139]. Particularly, a generalized fluctuation-dissipation relation (FDR) was introduced, which provides a statistical basis for extending the definition of temperature to far-from-equilibrium classical systems.…”
Section: Physical Motivations To Extend the Concept Of Temperature Oumentioning
confidence: 99%
See 1 more Smart Citation
“…They have concluded that under the local equilibrium condition, different definitions give the same temperature, while in a non-equilibrium state beyond local equilibrium, the values of temperature defined by different approaches may deviate from one another. Puglisi et al have reviewed different definitions of temperature in classical systems and discussed their relevance to energy fluctuations [139]. Particularly, a generalized fluctuation-dissipation relation (FDR) was introduced, which provides a statistical basis for extending the definition of temperature to far-from-equilibrium classical systems.…”
Section: Physical Motivations To Extend the Concept Of Temperature Oumentioning
confidence: 99%
“…The direct application of Eq. (15) to open quantum systems is difficult [139,146], because different definitions of entropy do not lead to a consistent value even at the same temperature [147,148]. For example, the von Neumann entropy of the reduced system, S VN ≡ −tr S (ρ S ln ρ S ), has been used to define the local temperature via Eq.…”
Section: Physical Motivations To Extend the Concept Of Temperature Oumentioning
confidence: 99%
“…The concept of temperature used in thermodynamics and statistical mechanics [1] is also used in subatomic physics due to similar thermal and statistical property. At least the initial, chemical freeze-out, thermal or kinetic freeze-out, and effective temperatures are used in high energy collisions.…”
Section: Introductionmentioning
confidence: 99%
“…Our work represents an update of the previous review 13 . The interested reader can find more exhaustive reviews of the general subject in 12,[14][15][16][17][18] . For a more rigorous discussion see also 19 .…”
Section: Introductionmentioning
confidence: 99%